Empowering Islamic Boarding Schools through Collaborative Management for Recognized and Sustainable Quality Education - Sari, Rara Novita; Nurilhaq, Emily Ghaitsa (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Islamic boarding schools (pesantren) are the oldest Islamic educational institutions in Indonesia and play a vital role in shaping the nation's morals and character. With the changing times and technological advancements, Islamic boarding schools face the challenge of remaining relevant and competitive with other educational institutions. This study aims to examine how the application of collaborative management can empower Islamic boarding schools to create quality, recognized, and sustainable education. The research method used is a Systematic Literature Review (SLR) using the PRISMA model. The study was conducted on eight scientific articles published between 2020 and 2025, selected based on the criteria of relevance, open access, and contextual suitability to the theme of Islamic boarding school empowerment and management. The analysis was conducted using content analysis to identify key themes related to institutional empowerment, human resource strengthening, and quality assurance systems. The study's results indicate that collaborative management plays a crucial role in enhancing the quality and sustainability of Islamic boarding schools. Collaboration involving internal elements—such as kiai, teachers, and students—as well as external elements, including the community, government, and partner institutions, can create governance that is more participatory and adaptive to the needs of the time. Human resource empowerment is a primary focus through training, competency development, and teacher regeneration. Furthermore, some Islamic boarding schools are beginning to integrate Islamic values. Sustainable Development Goals(SDGs) in the curriculum and learning activities to foster social and environmental awareness among students. Overall, the implementation of collaborative management has been proven to encourage Islamic boarding schools to become more independent, professional, and competitive institutions without abandoning their Islamic identity. Thus, Islamic boarding schools have the potential to become models of quality and sustainable Islamic education in the modern era.